Farm efficiency related to animal welfare performance and management of sheep farms in marginal areas of Central Italy: a two-stage DEA model. Issue 1 (1st January 2021) - Cecchini, Lucio; Vieceli, Laura; D'Urso, Adriano; Magistrali, Chiara Francesca; Forte, Claudio; Mignacca, Sebastian Alessandro; Trabalza-Marinucci, Massimo; Chiorri, Massimo
Abstract: The development of specific actions to increase animal health and welfare is indicated as a strategy to improve the efficiency and sustainability of many livestock systems, including sheep farming. In this paper, efficiency measures are provided to confirm the hypothesis that farms that are higher-performing in terms of animal welfare and management are also more technically efficient. A two-stage Data Envelopment Analysis (DEA) approach was adopted with the following twofold objectives: 1) to evaluate the efficiency and super-efficiency of 76 meat-producing sheep farms situated in marginal lands in central Italy, through DEA and Super-DEA (S-DEA) models; and 2) to assess the influence of animal welfare and management indicators on technical efficiency values through the application of a Tobit regression model. An overall efficiency performance varying within a range of 0.44–1 was estimated, with an average value of 0.80, implying a potential increase of 20% in terms of output production from both management and scale improvements. The 'pure' technical inefficiency was found to contribute three times more than scale inefficiency in determining the overall technical inefficiency. Adopting a more extensive farming system and increasing replacement rate were found to affect negatively the efficiency scores. On the other hand, having less than 5% of animals with body condition score beyond acceptable limits, presence of access control structures, well managed lambing pens, and dedicated feed stocking areas resulted in a positive influence on efficiency. Improvements in animal welfare aspects did not appear to be farm-scale-dependent. Highlights: DEA and Super-DEA models were applied to assess sheep farm technical efficiency in Central Italy. An overall potential 20% increase in output production was estimated. Animal welfare factors were found to significantly affect efficiency performance.